A INTEGRASI NILAI KEISLAMAN DALAM PENGUATAN CRITICAL THINKING DAN PROBLEM SOLVING SISWA: KAJIAN KONSEPTUAL PERSPEKTIF PENDIDIKAN ISLAM - M. Soinun Amrillah; Leny Misdiyanti; M. Sirozi (TA'LIM : Jurnal Studi Pendidikan Islam, 2026)
Integration of Islamic values ​​in strengthening students' critical thinking skills and problem solving competencies in the context of 21st century learning. Global challenges as emphasized in the 21st Century Skills framework and the OECD report place critical thinking and problem solving as essential competencies that must be developed systematically. However, strengthening these competencies requires a foundation of values ​​so that they cannot be separated from ethical and spiritual orientation. This research uses a qualitative approach based on literature study by analyzing national and international journal sources related to critical thinking, problem solving, and Islamic education. The results of the study show that the integration of Islamic values ​​such as ṣidq (honesty), 'adl (justice), amanah (responsibility), and shūrā (deliberation) can strengthen critical thinking dispositions through the habit of reflection, rational argumentation, and value-based decision making. This integrative implementation is effectively implemented through problem based learning models, project based learning, and the development of HOTS based teaching materials. Thus, the integration of Islamic values ​​not only increases students' cognitive achievements, but also forms a reflective and solution character in dealing with life's problems contextually and responsibly.